2005
DOI: 10.1007/s11101-005-3261-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant Derived Antimalarial Agents: New Leads and Challenges

Abstract: New treatments for malaria are urgently needed due to the increasing problem of drug-resistance in malaria parasites. The long-established use of quinine and the more recent introduction of artemisinin and its derivatives as highly effective antimalarials demonstrates that plant species are an important resource for the discovery of new antimalarial agents. Furthermore, many plant species continue to be used in traditional medicines for the treatment of malaria and many people depend on such remedies as they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 27 publications
1
77
0
1
Order By: Relevance
“…Mortality exceeds 1-3 million people per year, most of them being children in Africa under the age of 4 years, a number that is continuously increasing due to the rapid spread of drug-resistant Plasmodium parasites (Greenwood & Mutabingwa, 2002;Schwikkard & van Heeden, 2002;Wright, 2005). After an antimalarial screening of Congolese medicinal plants, we have observed that the MeOH extract of Euphorbia hirta Linn (Euphorbiaceae) (OliverBever, 1986;Iwu, 1993) demonstrated not only potent in vitro antimalarial activity against P. falciparum but also little cytotoxic property against human epidermoid carcinoma KB 3-1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality exceeds 1-3 million people per year, most of them being children in Africa under the age of 4 years, a number that is continuously increasing due to the rapid spread of drug-resistant Plasmodium parasites (Greenwood & Mutabingwa, 2002;Schwikkard & van Heeden, 2002;Wright, 2005). After an antimalarial screening of Congolese medicinal plants, we have observed that the MeOH extract of Euphorbia hirta Linn (Euphorbiaceae) (OliverBever, 1986;Iwu, 1993) demonstrated not only potent in vitro antimalarial activity against P. falciparum but also little cytotoxic property against human epidermoid carcinoma KB 3-1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products of various structural types have shown antiparasitic potency in the laboratory, and they represent interesting lead structures for the development of new drugs (12). The molecular diversity and efficacy of antiparasitic plants, extracts, and herbal preparations have been intensively discussed in recent reviews (22,26,27).…”
mentioning
confidence: 99%
“…This is isolated from the roots of the climbing shrub Cryptolepis sanguinolenta (Lindi) Schitr (Alajarin et al, 1997) that is used in Central and West Africa in traditional medicine for the treatment of malaria (Wright, 2005).…”
Section: Research Articlementioning
confidence: 99%